Banana stem based activated carbon as a low-cost adsorbent for methylene blue removal: Isotherm, kinetics, and reusability - Erni Misran (Elsevier, 2022)
A low-cost activated carbon from the banana stem (ACBS) was produced to contribute to environmental preservation in removing methylene blue from wastewater. It is originated from abundant agricultural waste and produced at moderate pyrolysis temperature and short pyrolisis time. In the ACBS production, the banana stem was impregnated with H3PO4 solution as the activating agent and followed by pyrolysis at 400 °C for a rapid time of 15 min. The treatment significantly improved the ACBS surface area to 837.453 m2/g. The influence of the ACBS dose and initial concentration of dye solution at various contact times were investigated in this study. The utilization of ACBS in low doses exhibited high removal efficiency of methylene blue (0.05 to 0.3 g/100 mL). It can remove methylene blue completely in 90 min of adsorption with an initial concentration of 50 g/mL. High removal efficiencies are still also demonstrated at higher initial concentrations with 99.762% removal for the initial concentration of 200 g/mL. Equilibrium adsorption data had the best agreement to the Freundlich isotherm model and pseudo-second-order kinetics model. It is predicted that ACBS has a maximum adsorption capacity of 101.01 mg/g. ACBS is an environmentally benign and favorable adsorbent in methylene blue removal and also effective for repeated usage up to 6 consecutive times with no desorption step.